Applied Improvisation in Africa: Facilitating Embodiment Work in Online Rooms - Apotieri-Abdulai, Oluwadamilola; Janse Van Vuuren, Petro (Arts Research Africa, The Wits School of Arts, University of the Witwatersrand, 2020)
An important aspect of Applied Improvisation is using and perceiving the body and those of others in the room. Can adaptations be made to enable embodied work online without jeopardising impact? In this workshop, we present different improvisation methods that can be used in online settings.
An important aspect of Applied Improvisation is using and perceiving the body and those of others in the room. Can adaptations be made to enable embodied work online without jeopardising impact? In this workshop, we present different improvisation methods that can be used in online settings.
Keywords: artistic research, arts research, decolonisation, arts pedagogy